2021
DOI: 10.1002/jmri.27563
|View full text |Cite
|
Sign up to set email alerts
|

Brain Abscess Apparent Diffusion Coefficient is Associated With Microbial Culture Yields

Abstract: Background: Obtaining pus for microbial cultures is one of the surgical aims in patients with brain abscess. Predictors of microbial yields are necessary as they help in treatment planning. Purpose: To investigate the relationship between microbial culture yields of brain abscesses and their apparent diffusion coefficient (ADC) values and clinical characteristics. Study Type: Retrospective. Subjects: Eighty-four patients diagnosed with brain abscess by surgery and histopathology (59 with positive abscess cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Apparent diffusion coefficient (ADC) and fractional anisotropy (FA) are quantitative metrics derived from DTI for water diffusivity measurement. In addition to tumor cellularity ( 20 ) and fluid viscosity ( 21 ), they may also reflect the volume and flow directionality of the tumor interstitial fluid ( 12 ). The ALPS index, recently proposed by Taoka et al, is another quantitative diffusion metric derived from DTI ( 22 ).…”
Section: Introductionmentioning
confidence: 99%
“…Apparent diffusion coefficient (ADC) and fractional anisotropy (FA) are quantitative metrics derived from DTI for water diffusivity measurement. In addition to tumor cellularity ( 20 ) and fluid viscosity ( 21 ), they may also reflect the volume and flow directionality of the tumor interstitial fluid ( 12 ). The ALPS index, recently proposed by Taoka et al, is another quantitative diffusion metric derived from DTI ( 22 ).…”
Section: Introductionmentioning
confidence: 99%
“…The diffusion restriction in the central liquid portion of a pyogenic abscess is related to the viscosity of the pus and the presence of neutrophils. A recent study showed a lower Apparent Diffusion Coefficient (ADC) on positive culture abscesses than on negative ones [21], suggesting a correlation between ADC and bacterial culture yields. Thus, the ADC map could guide a needle biopsy if the lesions are multiple.…”
Section: Neuroimagingmentioning
confidence: 98%
“…In this issue of JMRI, Toh et al 7 investigated whether mean ADC values of cerebral abscesses could contribute to treatment planning through predicting whether the abscess may be culture positive or negative. For this purpose, they compared 84 cerebral abscesses (59 of them were culturepositive and 25 culture-negative) in terms of mean ADC values and found that the ADC values of culture-positive abscesses (841 AE 173 × 10 −6 mm 2 /sec) were significantly higher than ADC values of culture-negative ones (536 AE 90 × 10 −6 mm 2 /sec).…”
mentioning
confidence: 99%
“…Lee et al 1 reported that the abscess culture of a cerebral abscess with focal diffusion restriction was sterile while Streptococcus intermedius was found in the abscess culture of another case with heterogeneous diffusion. For these reasons, the results of Toh et al 7 need to be verified by prospective studies to be conducted using larger series with more homogeneous cases (eg, cases sub-grouped by active agents such as bacterial, fungal, or parasitic agents, by the abscess age if possible, by comorbid diseases or host immunity, etc. ).…”
mentioning
confidence: 99%